Implementing Mindfulness-Based Cognitive Therapy (MBCT) as mindfulness skills courses offered as an adjunct to individual therapy: a feasibility and effectiveness study of mixed staff and patient groups in secondary care. (18th May 2016) - Hortynska, Kamila; Masterson, Ciara; Connors, Lesley; Geary, Lesley; Winspear, Richard
Abstract: There is growing evidence regarding the effectiveness of mindfulness-based interventions offered to diagnostically diverse groups of participants. This study examined the feasibility and effectiveness of adapted Mindfulness-Based Cognitive Therapy (MBCT) groups offered to NHS patients in a secondary-care Psychology and Psychotherapy Service. The group was run as an adjunct to individual therapy and accepted referrals from all therapists in the service, so participants had experienced a range of therapeutic approaches prior to attending the group. The nine groups run during the project also included staff participants, as part of a capacity-building strategy. Results indicate high levels of acceptability, with low drop-out rates. Standardized outcome measures were used to examine the effectiveness of the group, and patient participants demonstrated improvements which were statistically significant. Qualitative feedback from group participants and referrers was positive. The findings support implementation of MBCT as part of a package of psychological therapy interventions. Further research regarding this form of MBCT is discussed.